MEASUREMENT OF MOVEMENT OF OBJECTS BY THE HETERODYNE METHOD - A. A. Titov; V. K. Garipov; M. A. Kostromin (Российский технологический журнал)
In this paper the issues of object movements measurement by the heterodyne method have been considered. It has been shown that nowadays in order to measure linear movements various kinds of methods are used. It has been found that interferential methods have the highest accuracy of measurements. It also has been defined that the majority of these methods is based on calculating the number of interferential fringes when objects shift, that does not allow to resolve ambiguity in the object location; and the interferential methods realization based on the frequency shift of interfering beams (heterodyne interferometry) are used for the absolute measurements of the object’s location. It has been demonstrated that when realizing these methods two-frequency lasers are required. As they are rather difficult optical and electronic systems, they hinder their application in measuring devices. The non-ambiguity resolution method in the definition of the object easurement range, allowing elimination of the drawbacks specified, has been offered.